2020
DOI: 10.7150/jca.40592
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG6 promotes proliferation and angiogenesis of cholangiocarcinoma cells through sponging miR-101-3p and activation of E2F8

Abstract: Cholangiocarcinoma (CCA) development is an extremely complex process with alterations occurring in numerous genes. SNHG6, a validated lncRNA, has been reported to regulate the expression of multiple tumor-related genes in hepatocellular carcinoma, colorectal cancer and breast cancer. Here, we elucidated the function and possible molecular mechanisms of SNHG6 in human CCA cells. Our results proved that the expression SNHG6 was upregulated in CCA tissues and cell lines. Ectopic expression of SNHG6 promoted cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…A previous study also showed that SNHG6 promoted the proliferation and angiogenesis of cholangiocarcinoma cells by sponging miR-101-3p. 27 These results confirmed that SNHG6 affects apoptosis in ESCC cells by regulating miR-101-3p expression.…”
Section: Dovepresssupporting
confidence: 67%
See 1 more Smart Citation
“…A previous study also showed that SNHG6 promoted the proliferation and angiogenesis of cholangiocarcinoma cells by sponging miR-101-3p. 27 These results confirmed that SNHG6 affects apoptosis in ESCC cells by regulating miR-101-3p expression.…”
Section: Dovepresssupporting
confidence: 67%
“…MiR-101-3p serves as a tumor suppressor gene in a variety of tumors including colorectal cancer, 18 gastric cancer, 26 and cholangiocarcinoma. 27 In the current study, we showed that miR-101-3p function as a tumor suppressor gene in ESCC. To confirm that SNHG6 affected apoptosis in ESCC cells by inhibiting miR-101-3p expression, we co-transfection si-SNHG6 and a miR-101-3p inhibitor and found that downregulation of miR-101-3p reversed its effects on apoptosis in SNHG6 knockdown cells.…”
Section: Dovepressmentioning
confidence: 56%
“…For example, SNHG6 acts as an oncogene to promote the tumorigenesis and development of colorectal cancer ( 10 ). Furthermore, SNHG6 promotes cholangiocarcinoma (CCA) cell progression, and its upregulation is associated with poor overall survival in patients with CCA ( 11 ). SNHG6 facilitates the proliferation and invasion of breast cancer cells by sponging microRNA (miRNA/miR)-26a and by upregulating vasodilator stimulated phosphoprotein expression ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lncRNA SNHG6 and DANCR were identified to accelerate angiogenesis in cholangiocarcinoma by competitively binding miRNAs, thus leading to an increased expression of transcriptional factors [ 135 , 137 ]. In detail, SNHG6 binds miR-101-3p to prevent the inhibition of the transcription of E2F Transcription Factor 8 (E2F8) [ 137 ], whereas the DANCR–miR-345-5p interaction upregulates Twist1. In osteosarcoma, proangiogenic lncRNA TUG1 functions via silencing miR-143-5p, increasing the miRNA target HIF-1α [ 139 ].…”
Section: Lncrnas Regulating Tumor Angiogenesis In Different Cancermentioning
confidence: 99%